Analysis of Financial Ratio to Measure Financial Performance PT Nippon Indosari Corpindo, Tbk - Daniel Marco Hutabarat; Matthew Alessandro Sianipar; Sutan Maulana; Yeftika Mutiara Sianturi (Asian Journal of Management Analytics, 2023)
In order to get a picture of the profitability of a company by using financial ratios as a measuring tool, this research was conducted to analyze the profitability of PT Nippon Indosari Corpindo, Tbk., from 2019–2022. The data analysis method used is a descriptive method with a quantitative approach using secondary data. The research results based on the results of financial ratio analysis show that the liquidity ratio is above the industry standard, which indicates a good condition. The debt-to-asset ratio has decreased, so the solvency ratio is in fairly good condition. The activity ratio has increased substantially in 2022. The company experienced a net loss, so the profitability ratio has decreased.